Temporal variation in translocated Isle Royale wolf diet. Issue 3 (16th March 2023) - Sovie, Adia R.; Romanski, Mark C.; Orning, Elizabeth K.; Marneweck, David G.; Nichols, Rachel; Moore, Seth; Belant, Jerrold L.
Abstract: Wolves ( Canis lupus ) can exert top‐down pressure and shape ecological communities through the predation of ungulates and beavers (Castor spp.). Therefore, understanding wolf foraging is critical to estimating their ecosystem‐level effects. Specifically, if wolves are consumers that optimize tradeoffs between the cost and benefits of prey acquisition, changes in these factors may lead to prey‐switching or negative‐density dependent selection with potential consequences for community stability. For wolves, factors affecting cost and benefits include prey vulnerability, risk, reward, and availability, which can vary temporally. We described the wolf diet by the frequency of occurrence and percent biomass and characterized the diet using prey remains found in wolf scats on Isle Royale National Park, Michigan, USA, during May–October 2019 and 2020. We used logistic regression to estimate prey consumption over time. We predicted prey with temporal variation in cost (availability and/or vulnerability) such as adult moose ( Alces alces ), calf moose, and beaver ( Castor canadensis ) to vary in wolf diets. We analyzed 206 scats and identified 62% of remains as beaver, 26% as moose, and 12% as other species (birds, smaller mammals, and wolves). Adult moose were more likely to occur in wolf scats in May when moose are in poor condition following winter. The occurrence of moose calves peaked during June–mid‐July following birth but before calf vulnerability declined as they matured. By contrast, beaver occurrence in wolf scat did not change over time, reflecting the importance of low‐handling cost prey items for recently introduced lone or paired wolves. Our results demonstrate that the wolf diet is responsive to temporal changes in prey costs. Temporal fluctuation in diet may influence wolves' ecological role if prey respond to increased predation risk by altering foraging or breeding behavior. Abstract : We analyzed wolf diet from scats in relation to optimal foraging. We found 62% of remains as beaver, 26% as moose, and 12% as other (birds, smaller mammals, and wolves). The contents of wolf scat changed over time. Wolf diet is plastic and responsive to temporal changes in prey acquisition cost as predicted by optimal foraging theory.